2007
DOI: 10.7828/ljher.v5i1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Culture of Excellence of Private Higher Education Institutions

Abstract: -The study investigated the culture of excellence of six top performing private higher education institutions in Northern Mindanao. These descriptive study respondents involved 80 academic administrators and program chairpersons as respondents. The frequency, percentage, weighted mean, and analysis of variance were used. These are the conclusions of the study. The culture of excellence is largely a function of efficient and effective quality assurance management systems such as voluntary accreditation and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This has been observed even before the pandemic period among HEIs. Japos (2022) reported that the CoE greatly influences HEIs in responding to the demands of the society manifested through their high employability, passing rate in licensure examinations, and global competitiveness. This encompasses the quality of teaching and research, support to students, relations with the community, and management of resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been observed even before the pandemic period among HEIs. Japos (2022) reported that the CoE greatly influences HEIs in responding to the demands of the society manifested through their high employability, passing rate in licensure examinations, and global competitiveness. This encompasses the quality of teaching and research, support to students, relations with the community, and management of resources.…”
Section: Introductionmentioning
confidence: 99%
“…46, Series of 2012 which layouts the landscape on how HEIs can be center of excellence in their respective niche. To substantiate, some HEIs undergo accreditation to ensure high standards are met and being offered to their stakeholders (Japos, 2022). As posited by Kumar et al (2020), accreditation can really enhance the excellence of HEIs.…”
Section: Introductionmentioning
confidence: 99%